(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In the industrialized world, burnout, distress, and sick leave are significantly higher among healthcare workers than in other industries. Interest in enhancing the emotional and physical well-being of healthcare professionals has grown as a result of the growing load that rapidly aging populations and rising rates of chronic disease burdens are placing on healthcare systems and, consequently, healthcare workers. The physical and/or mental health of healthcare workers improved, and healthier behaviours were encouraged, as a result of interventions that incorporated at least one of the five whole-system recommendations for enhancing healthcare worker health and wellbeing. Nevertheless, after implementing all five suggestions in their workplace social capital intervention, one study found no statistically significant difference in the workplace social capital measure of mental health. The project aims to explore patient-cantered treatment and the role of public health in promoting community wellness. The roles of labs, nursing, and health informatics were also covered.